2016
DOI: 10.1038/npp.2016.273
|View full text |Cite
|
Sign up to set email alerts
|

GABAb Receptor Mediates Opposing Adaptations of GABA Release From Two Types of Prefrontal Interneurons After Observational Fear

Abstract: The observational fear (OF) paradigm in rodents, in which the subject is exposed to a distressed conspecific, elicits contextual fear learning and enhances future passive avoidance learning, which may model certain behavioral traits resulting from traumatic experiences in humans. As these behaviors affected by the OF require dorso-medial prefrontal cortex (dmPFC), we searched for synaptic adaptations in dmPFC resulting from OF in mice by recording synaptic responses in dmPFC layer V pyramidal neurons elicited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 55 publications
0
15
0
1
Order By: Relevance
“…A comparison was made between slices expressing "high" and "low" levels of ChR2-YFP, which were obtained from animals transduced with 1 x 10 8 To examine the role of GABAb receptor in the synaptic plasticity, IPSCs were recorded first in ACSF without drugs and then, after 10 min perfusion with 10 µM of CGP52432, a GABAb receptor blocker. The IPSC data from the low virus slices are a part of an earlier publication (6), but are included here to allow for the comparison between the high and low virus conditions. The IPSC amplitudes decreased along the train in both the low and the high virus groups (low virus: F(4,10) = 121, p<0.0001; high virus: F(4, 9) = 82, p<0.0001), but the decreases in the low virus group were greater ("train" * "level of virus" interaction, F (4,19) = 17.4, p<0.0001) (Fig.1E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison was made between slices expressing "high" and "low" levels of ChR2-YFP, which were obtained from animals transduced with 1 x 10 8 To examine the role of GABAb receptor in the synaptic plasticity, IPSCs were recorded first in ACSF without drugs and then, after 10 min perfusion with 10 µM of CGP52432, a GABAb receptor blocker. The IPSC data from the low virus slices are a part of an earlier publication (6), but are included here to allow for the comparison between the high and low virus conditions. The IPSC amplitudes decreased along the train in both the low and the high virus groups (low virus: F(4,10) = 121, p<0.0001; high virus: F(4, 9) = 82, p<0.0001), but the decreases in the low virus group were greater ("train" * "level of virus" interaction, F (4,19) = 17.4, p<0.0001) (Fig.1E).…”
Section: Resultsmentioning
confidence: 99%
“…Electrophysiology. Slice preparation and recordings were performed as described in (6). Coronal dmPFC slices, 300 µm thickness, were prepared from p60-75 mice using DSK Microslicer (Ted Pella, Redding, CA) and ice cold cutting solution contained (in mM) 110 Choline Cl, 2.5 KCl, 1.2 NaH 2 PO 4 , 2.5 NaHCO 3 , 20 glucose, 0.5 CaCl 2 , and 5 MgSO 4 , bubbled with a 95% O 2 /5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because PV neurons generally target the somas of pyramidal neurons, whereas dendrite-targeting SST neurons exert distal inhibition to control incoming inputs to pyramidal neurons (Gentet et al, 2012;Tremblay et al, 2016), these findings suggest that SST neuron-specific inhibitory mechanisms in the ACC microcircuit are responsible for vicarious transmission of social fear. Following observational fear learning, ex vivo slice recording showed that the inhibitory drive was shifted from the soma to the distal dendrites of pyramidal neurons in the ACC (Liu et al, 2017). It is yet to be determined what physiological function this plasticity has.…”
Section: Cortical Microcircuitry In Observational Fearmentioning
confidence: 99%
“…Notably, the distribution and action of GABA-B receptors may not be homogenous throughout the network. Research in the prefrontal cortex has shown that presynaptic GABA-B activation causes short-term depression of inhibitory inputs, and that inputs from somatostatin (SST)-expressing interneurons (SST-INs) are more strongly affected than those of parvalbumin (PV)-expressing interneurons (Liu et al, 2017). Hub cells that strongly influence SSNA tend to be SST-INs (Mòdol et al, 2017).…”
Section: Synaptic Mechanisms Of Network Activitymentioning
confidence: 99%